Optimasi Pengiriman Sapi Potong pada Jaringan Pelayaran Kapal Khusus Ternak dengan Algoritma Genetika - Natalia, Christine; Setiadi, Ghea Ghoniyyah; Silalahi, Agustinus (Metris: Jurnal Sains dan Teknologi, 2019)
The government livestock carrier cruise program is a dedicated program to improve the supply chain management of livestock and the ultimate goal is selfsufficiency of beef in 2026. This carrier has one fleet with the capacity of 500 cows and sails through 8 ports regularly. The island of Nusa Tenggara are the local producers for the livestock carrier cruise which is an area of provincial surplus of beef. For the future the government plans to add more ships to the armada from the current one fleet to six fleets of livestock carrier cruises. The current livestock carrier cruise program has not been optimal in shipping cows to the consumer area. This is caused by the limitation of number of fleet and theexisting route that the livestock carrier has to sail through has created some obstacle to maximizing the number of cows to be distributed. This research aims to optimise this carrier cruising route with criteria including having high supplied beef percentage rate and having the most minimum cost. This optimisation problem solved by genetics algorithm methid and develop twodifferent scenarios that suggest alternatives for an optimal route. To make things easier, a computerized program with genetics algorithm method for a livestock carrier cruise optimization network are designed. The outcome of this research is a proposed optimised route on scenario 1 with total cost of Rp 443,306,533.26, and total load of 1,374 cows. As for the future to add five ships, the conditions are met by using the results of the second scenario with total cost of Rp 1,321,505,850.62, total load of 3416 cows and the route network for six ships